2002
DOI: 10.1111/1467-8624.00491
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Influences on Adjustment in Early Adolescence: Investigation of an Integrative Model

Abstract: This research investigated an integrative model of race- and gender-related influences on adjustment during early adolescence using a sample of 350 Black and White youth. In the proposed model, prejudice/discrimination events, as well as race and gender daily hassles, contribute to a general stress context. The stress context, in turn, influences levels of emotional and behavioral problems in adjustment, with these associations mediated (in part) by intervening effects on self-esteem. Racial and gender identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
143
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(162 citation statements)
references
References 69 publications
14
143
2
2
Order By: Relevance
“…Therefore with the exception of connectedness, where low score showing less connectedness rather resulted in high self-esteem, the rest correlated in a good dimension because the low scores indicating low anxiety or unease perception, more dependent and more peaceful relationships produced students with high self-esteem even though the correlations were not statistically significant (p> 0.05, Table 2). This finding supported the propositions that good relationship between learners and the instructors provide a perfect atmosphere for the learner, promoting social acceptance and belonging and in turn inspire the learner to esteem high in life (DeSantis et al, 2006, DuBois et al, 2002Hamilton & Howes, 1992;Gatabu, 2013). This clearly revealed that environment play an important role in developing high self-esteem.…”
Section: Journal Of Social Science Studiessupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore with the exception of connectedness, where low score showing less connectedness rather resulted in high self-esteem, the rest correlated in a good dimension because the low scores indicating low anxiety or unease perception, more dependent and more peaceful relationships produced students with high self-esteem even though the correlations were not statistically significant (p> 0.05, Table 2). This finding supported the propositions that good relationship between learners and the instructors provide a perfect atmosphere for the learner, promoting social acceptance and belonging and in turn inspire the learner to esteem high in life (DeSantis et al, 2006, DuBois et al, 2002Hamilton & Howes, 1992;Gatabu, 2013). This clearly revealed that environment play an important role in developing high self-esteem.…”
Section: Journal Of Social Science Studiessupporting
confidence: 76%
“…Because great amount of time and working hours were spent by students at school, the time investment indicated the important impact of learning environment on their learning (Larson, 2010) of which the teachers are the key influencers in this learning environment. DuBois et al (2002) revealed that environment has been shown to play important role in determining trajectories of adolescents' self-esteem. The type and quality of teacher-student relationships and academic achievement have both been directly linked to high self-esteem attainment (Hamilton & Howes, 1992).…”
Section: Review Of Related Literaturesmentioning
confidence: 99%
“…Taken together, this research provides some evidence that discrimination, prejudice and other disadvantages in school settings is associated with negative educational outcomes among African American adolescents. Indeed, researchers have posited that the stress youth experience within a context should affect their engagement within that setting (DuBois et al, 2002). With this in mind, the current investigation explored whether relationships between school racial climate and academic achievement were mediated by youths' school engagement.…”
Section: Racial Climate and Achievement Outcomesmentioning
confidence: 98%
“…In particular, peer interactions may serve as a context in which minority youth experience racially motivated social exclusion or harassment (Scott, 2004;. Previous research supports this assertion and indicates that adolescent youth perceive differential treatment from same-age peers (DuBois, Burk-Braxton, Swenson, Tevendale & Hardesty, 2002;Fisher et al, 2000;. Peer racial discrimination manifests in multiple ways, including intentional or overt social exclusion, teasing, hitting, and unfair treatment based on ethnic group membership (Brown & Bigler, 2005;Chavous et al, 2008;Greene et al, 2006;Rosenbloom & Way, 2004;Verkuyten & Steenhuis, 2005;.…”
Section: Racial Climate and Schoolingmentioning
confidence: 99%
See 1 more Smart Citation